Adverse obstetric outcomes in congenital Müllerian anomalies: experience from a high-risk pregnancy unit - Farheen, Khateeb; Mehta, Prakash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Congenital Müllerian anomalies are associated with increased risk of adverse obstetric outcomes. Data from Indian centers remain limited, especially from high‑risk obstetric units. Methods: A 10‑year retrospective record‑based cross‑sectional analysis was conducted at a tertiary care center from August 2011 to July 2021. A total of 53 pregnant women diagnosed with congenital uterine anomalies were included. Outcomes assessed included preterm birth, abortions, PPROM, malpresentation, fetal growth restriction, and placenta accreta spectrum/postpartum hemorrhage.. Results: The most common anomaly was bicornuate uterus (41.5%, n=22), followed by unicornuate uterus (26.3%, n=14), septate/subseptate uterus (15%, n=8), arcuate uterus (15%, n=8), and uterus didelphys (n=1). Preterm birth occurred in 30 women (56.6%), abortion in 13 (24.5%), PPROM in 11 (20.7%), malpresentation in 15 (28.3%), fetal growth restriction in 15 (28.3%), and placenta accreta spectrum and/or postpartum hemorrhage in 10 cases (18.8%). Conclusions: Congenital Müllerian anomalies substantially increase obstetric risk, particularly preterm birth, PPROM, malpresentation, and hemorrhage. Early identification and risk‑stratified antenatal surveillance are essential in resource‑limited settings.